Tradeoffs between self-interest and other-regarding preferences cause willpower depletion - Hanna Fromell; Daniele Nosenzo; Trudy Owens (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2014)
In this paper we show that making choices that involve conflicts between self-interest and otherregarding concerns may deplete cognitive resources and willpower and thus reduce individuals' ability to exert self-control. In a lab experiment we use a series of modified dictator games to manipulate whether subjects are exposed to tradeoffs between their self-interest and the interest of others: in a Conflict treatment the option that maximizes the dictator's payoff always minimizes the recipient's payoff, whereas in the NoConflict treatment dictator's and recipient's payoffs are aligned. We then measure how decision-making in the dictator games affects subjects' performance in a subsequent and unrelated task that requires exertion of willpower. We find that subjects in the Conflict treatment perform significantly worse than those in NoConflict. This effect is particularly marked for dictators who experienced a stronger conflict during the dictator games.
Keywords: C91; 330; other-regarding preferences; willpower; self-control; depletion; dictator game; Stroop task